IMPLEMENTASI SISTEM PENGENDALIAN INTERN PEMERINTAH (STUDI EMPIRIS PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN BENGKULU TENGAH) - Afrianto, Jamil (Institut Agama Islam Bengkulu, 2016)
This research is quantitative research looking at the implementation of the governmentâ€™s internal control system of local government performance: the structural official involvement as moderating variable at the official work unit, the District of Central Bengkulu. Data were obtained through questionnaires in 243 officers in all offices of the local work unit the district of Central Bengkulu. The analytical method used is a multiple linier regression by using statistical software. The results showed that the application of the system of internal control in the government agencies working unit in Central Bengkulu proved to affect the performance of official work unit in Central Bengkulu. The Structural official involvement proved to strengthen the implementation of internal control systems in the government work unit of central Bengkulu. The office work unit at Central Bengkulu has implemented the internal control system with good government.Â Keywords : Intern Government Control System, Structural Official Involvement,Local Government Performance